2010
DOI: 10.1089/scd.2009.0041
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Long-Term Cultured c-kit+Cardiac Stem Cells Derived From Adult Rat Hearts

Abstract: Previous studies have revealed c-kit-positive (c-kit(+)) cardiac stem cells (CSCs) in the adult mammalian heart and these cells could be a suitable cell source for heart regeneration therapy. However, these cells have not been fully evaluated in terms of characterization and effect of long-term culture, which is necessary for their safe and optimal usage. Therefore, we isolated c-kit(+) CSCs from adult rat hearts to characterize these cells and investigate stability over long-term culture. We performed isolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
135
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(140 citation statements)
references
References 57 publications
3
135
2
Order By: Relevance
“…The isolation of CSCs is the same as described before (31). Myocardial tissues from 3-mo-old CD-1 male mice were minced into small pieces and subjected to enzymatic dissociation, and the remaining tissue fragments were cultured as explants in explant medium [Iscove's Modified Dulbecco's IMDM with 10% fetal calf serum (FBS), 100 U/ml penicillin G, 100 g/ml streptomycin, 2 mmol/l L-glutamine, and 0.1 mmol/l 2-mercaptoethanol] at 37°C and 5% CO 2.…”
Section: Methodsmentioning
confidence: 99%
“…The isolation of CSCs is the same as described before (31). Myocardial tissues from 3-mo-old CD-1 male mice were minced into small pieces and subjected to enzymatic dissociation, and the remaining tissue fragments were cultured as explants in explant medium [Iscove's Modified Dulbecco's IMDM with 10% fetal calf serum (FBS), 100 U/ml penicillin G, 100 g/ml streptomycin, 2 mmol/l L-glutamine, and 0.1 mmol/l 2-mercaptoethanol] at 37°C and 5% CO 2.…”
Section: Methodsmentioning
confidence: 99%
“…Sca1+ CSCs CD34-, CD45-, FLK1-, ckit+/-, GATA4+, NKX2-5+/-, MEF2C+ (Oh et al, 2003;Forte et al, 2008;Matsuura et al, 2004;Rosenblatt-Velin et al, 2005;Tateishi et al, 2007;Wang et al, 2006;Wu et al, 2006) c-kit+ CSCs CD34-, CD45-, Sca1+, GATA4+, NKX2-5+, MEF2C+ Beltrami et al, 2003;Dawn et al, 2005;Linke et al, 2005;Miyamoto et al, 2010;Tillmanns et al, 2008;Urbanek et al, 2003) Isl-1+ CSCs CD31-, Sca1-, c-kit-, GATA4+, NKX2-5+ (Laugwitz et al, 2005;Moretti et al, 2006) Side population (SP Due to the importance of heart as a vital organ, several attempts have been made to characterize CSCs using various techniques. Numerous review articles were published covering the field of CSCs (Anversa et al, 2006;Bollini et al, 2011;Di Nardo et al, 2010;Musunuru et al, 2010;Tateishi et al, 2008).…”
Section: Type Of Cscs Other Markers Referencesmentioning
confidence: 99%
“…Considering the acclaimed types of CSCs, it seems that heart, once considered to be a post-mitotic organ, harbours the highest number of adult stem cells in the body. At present, it is not clear whether CSCs can be called "true" adult stem cells with a "true" multipotency (Ellison et al, 2010;Stamm et al, 2009). The concept of multipotent adult stem cells and progenitor cells (sometime classified as "transient-amplifying cells") (Bryder et al, 2006) is derived from the haematopoietic system and might not necessarily apply to CSCs.…”
Section: Type Of Cscs Other Markers Referencesmentioning
confidence: 99%
“…The results suggested that these CSCs retained multiple developmental potential to some extent. Consequently, we investigated these CSCs in detail, hoping to establish the regeneration method by using c-Kit-positive cardiac cells [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%